A novel flexible cuff-like microelectrode for dual purpose, acute and chronic electrical interfacing with the mouse cervical vagus nerve. (1st November 2017) - Caravaca, A S; Tsaava, T; Goldman, L; Silverman, H; Riggott, G; Chavan, S S; Bouton, C; Tracey, K J; Desimone, R; Boyden, E S; Sohal, H S; Olofsson, P S
Abstract: Objective . Neural reflexes regulate immune responses and homeostasis. Advances in bioelectronic medicine indicate that electrical stimulation of the vagus nerve can be used to treat inflammatory disease, yet the understanding of neural signals that regulate inflammation is incomplete. Current interfaces with the vagus nerve do not permit effective chronic stimulation or recording in mouse models, which is vital to studying the molecular and neurophysiological mechanisms that control inflammation homeostasis in health and disease. We developed an implantable, dual purpose, multi-channel, flexible 'microelectrode' array, for recording and stimulation of the mouse vagus nerve. Approach . The array was microfabricated on an 8 µ m layer of highly biocompatible parylene configured with 16 sites. The microelectrode was evaluated by studying the recording and stimulation performance. Mice were chronically implanted with devices for up to 12 weeks. Main results . Using the microelectrode in vivo, high fidelity signals were recorded during physiological challenges (e.g potassium chloride and interleukin-1 β ), and electrical stimulation of the vagus nerve produced the expected significant reduction of blood levels of tumor necrosis factor (TNF) in endotoxemia. Inflammatory cell infiltration at the microelectrode 12 weeks of implantation was limited according to radial distribution analysis of inflammatory cells. Significance . This novel device provides an important step towards a viable chronic interface for cervical vagus nerve stimulation and recording in mice.